Factors influencing experience in crowds – The participant perspective. (March 2017) - Filingeri, Victoria; Eason, Ken; Waterson, Patrick; Haslam, Roger
Abstract: Humans encounter crowd situations on a daily basis, resulting in both negative and positive experiences. Understanding how to optimise the participant experience of crowds is important. In the study presented in this paper, 5 focus groups were conducted (35 participants, age range: 21–71 years) and 55 crowd situations observed (e.g. transport hubs, sport events, retail situations). Influences on participant experience in crowds identified by the focus groups and observations included: physical design of crowd space and facilities (layout, queuing strategies), crowd movement (monitoring capacity, pedestrian flow), communication and information (signage, wayfinding), comfort and welfare (provision of facilities, environmental comfort), and public order. It was found that important aspects affecting participant experience are often not considered systematically in the planning of events or crowd situations. The findings point to human factors aspects of crowds being overlooked, with the experiences of participants often poor. Highlights: Influences on participant experience in crowds using focus groups and observations. Previous research and attention largely focuses on safety of crowd participants. Participant experience is often not considered systematically during planning. Comfort and satisfaction in crowds are often overlooked and experiences often poor. Recommend a human factors systems approach embracing participant centered design.